Lavandula dentata L. sob o efeito da radiação solar e de diferentes épocas de colheita - Mambri, Ana Paula de Souza (2016)
Lavandula genus plants are known by a variety of volatiles and used for centuries in perfumes and medicinal applications. Several species in the world with productive potential, for example, Lavandula dentata L. species grown in many countries which includes Brazil, to aromatic and medicinal purposes. In addition to the diversity of varieties of lavender plants are quite resistant to adverse conditions of weather and temperature. There are many features that differentiate them from their morphological characters to the constitution of their volatile oils that have ecological functions well established in the plant. And there can be intraspecific variation of these compounds, and these differences can be related to the plant interactions with the environment, which trigger various biochemical processes that result in differences both in proportion as the phytochemical composition of the volatile oil. Natural products, such as volatile oil has been intensively studied for its productive aspects and biological activities. This study aimed to determine the effect of two intensities of solar radiation, and different harvesting times in biomass production, yield and chemical composition of the volatile oil from leaves and L. dentata plant inflorescences in soilless cultivation and how to evaluate the antimicrobial activity, genotoxic and antiproliferative the volatile compound. The experiment was conducted in a greenhouse in a closed system, the plants were grown in nutrient solution in polypropylene pots containing sand as substrate. They were collected for each harvest leaves and inflorescences to determine the fresh and dry weight of plants. The remaining green mass of each plot was used for the extraction of volatile oil by hydrodistillation method and the composition determined by gas chromatography (GC / MS). We used a completely randomized design, the biomass data and income were submitted ANOVA and the variables that showed significant differences were determined by Tukey test, the genotoxicity data were compared using the chi-square test (X²). We evaluated the aboveground biomass production and essential oil of lavender in two radiation intensity (with and without shading), at different times of collection (150, 213 and 320) days after planting. And also assess the antimicrobial effect by the method and bioautography genotoxicity oil concentrations (100%) and (0.05%), respectively. The oil yield, fresh weight (MF) and dry (MS) leaves (F) and inflorescences (I) were affected by shading and different times of collection, (MFI) was higher in the spring harvest (213 DAP ) without shading and (MFF), while for leaves the best time was in the summer period (320 DAP), and there was no effect on the use of 50% shading to (MF). However, there was a reduction in average values of MSF and MSI. The production of volatile oil in the leaves was higher in all collections held in the summer, to 320 DAP. The major constituents found in the volatile oil were 1.8 cineole, camphor and linalool. The oil (100%) showed moderate activity against the bacteria Staphylococcus aureus, Bacillus cereus and Salmonella typhimurium, the volatile oil (0.05%) from lavender showed no antiproliferative activity or genotoxic effect.